Research on Near-Fault Problems in Earthquake Engineering - Chengjiang Lu (Institute of Advanced Engineering and Science, 2012)
The state-of-the-art of near-fault problems in earthquake engineering is comprehensive reviewed. Strong ground motions in the near-fault region exhibit several new characteristics, which cause the attentions of both seismologists and engineers who zealously studied these ground motions during the last two deceases. The investigation on ground motions can interpret the mechanism of the earthquake. Also the ground motions, which are usually assigned by engineers as a type of input loading for seismic design of structures, can sometimes control the final design result. Hence, the characteristics of the loading and the corresponding response of structures are desired for studying. This paper deals with the inherent characteristics of near-fault ground motions and the influences of near-fault ground motions on civil structures. Existing problems are pointed out and work needing further investigation in the future is also discussed. DOI:http://dx.doi.org/10.11591/telkomnika.v10i5.1279